2001
DOI: 10.1080/15287390151101529
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cholinesterase Enzymes Following a Single Dermal Dose of Chlorpyrifos and Methyl Parathion, Alone and in Combination, in Pregnant Rats

Abstract: Pregnant Sprague-Dawley rats (14-18 d of gestation) were treated with either a single dermal subclinical dose of 30 mg/kg (15% of dermal LD50) chlorpyrifos (O,O-diethyl-O-[3,5,6-trichloro-2-pyridinyl] phosphorothioate) or a single dermal subclinical dose of 10 mg/kg (15% of dermal LD50) methyl parathion (O,O-dimethyl O-4-nitrophenyl phosphorothioate) or the two in combination. Chlorpyrifos inhibited maternal and fetal brain acetylcholinesterase (AChE) activity within 24 h of dosing, (48% and 67% of control act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Male offspring from mothers treated with either chlorpyrifos or nicotine alone showed a significant increase in AChE activity in the brainstem while female offspring from mothers treated with either nicotine or a combination of nicotine and chlorpyrifos showed a significant increase ($134 and 126% of control, respectively) in AChE activity in the brainstem. Maternal exposure to high doses of chlorpyrifos to developing fetus or pups produced inhibition of AChE in the maternal as well as the fetal (developing) rat (Lassiter et al 1998a(Lassiter et al , 1998b(Lassiter et al , 1999Abu-Qare et al 2001;Ashry et al 2002). The real-life exposure dose of chlorpyrifos in the present study is too small to produce any significant inhibitory effect on AChE.…”
Section: Discussionmentioning
confidence: 48%
“…Male offspring from mothers treated with either chlorpyrifos or nicotine alone showed a significant increase in AChE activity in the brainstem while female offspring from mothers treated with either nicotine or a combination of nicotine and chlorpyrifos showed a significant increase ($134 and 126% of control, respectively) in AChE activity in the brainstem. Maternal exposure to high doses of chlorpyrifos to developing fetus or pups produced inhibition of AChE in the maternal as well as the fetal (developing) rat (Lassiter et al 1998a(Lassiter et al , 1998b(Lassiter et al , 1999Abu-Qare et al 2001;Ashry et al 2002). The real-life exposure dose of chlorpyrifos in the present study is too small to produce any significant inhibitory effect on AChE.…”
Section: Discussionmentioning
confidence: 48%
“…Individuals with histories of exposure to low, sub-clinical levels of chlorpyrifos have also reported reduced levels of concentration, word finding and short-term-memory impairment [5]. CPF has also been reported to produce neurobehavioral and morphological damages in the nervous systems of animals during embryonic life through to postnatal development [6,7]. Previous work by the authors has found that sub-toxic doses (1/5th and 1/2 LD 50 ) of chlorpyrifos applied dermally for 3 weeks can produce significant hippocampal neuronal loss, and that stress can exacerbate this damage [8].…”
Section: Introductionmentioning
confidence: 99%
“…25) Treatment with of dichlorvos and lambda-cyhalothrin resulted in a statistically significant decrease in acetyl cholinesterase activity in each case; the inhibition of acetylcholinesterase activity might be due to direct interaction of the pesticide with enzymes. 26) Glucose-6-phosphate dehydrogenase is an important enzyme of the hexose monophosphate shunt; its functions in mature red blood cells (erythrocytes) is to generate NADPH, which is required for the conversion of oxidized glutathione (GSSG) to GSH, thus protecting the cell from oxidative damage, which, in turn, is necessary for the membrane integrity of erythrocyte membranes. 27) This might be the reason for the increased fragility of erythrocytes upon treatment with different pesticides.…”
Section: Discussionmentioning
confidence: 99%